If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 18 = -4(2x + -7) Combine like terms: 10 + 18 = 28 28 = -4(2x + -7) Reorder the terms: 28 = -4(-7 + 2x) 28 = (-7 * -4 + 2x * -4) 28 = (28 + -8x) Add '-28' to each side of the equation. 28 + -28 = 28 + -28 + -8x Combine like terms: 28 + -28 = 0 0 = 28 + -28 + -8x Combine like terms: 28 + -28 = 0 0 = 0 + -8x 0 = -8x Solving 0 = -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 0 + 8x = -8x + 8x Remove the zero: 8x = -8x + 8x Combine like terms: -8x + 8x = 0 8x = 0 Divide each side by '8'. x = 0 Simplifying x = 0
| 4x+5=9x+25 | | 3.3+x=5 | | x^2+y^2+z=27 | | 9-3(4y+6)=0 | | X+24=9x+56 | | 8=x(x-2) | | X-6=46 | | x/2-314=123 | | 10x-1447=933 | | -7+7=25 | | -10(s+3)=-13 | | cos(40)=x/14 | | 2y+5-1=15 | | 4(4s+4)=96 | | 7(2l+1)=77 | | 2(a-6)=34 | | (u-6)*10=100 | | 5/12x-3/4(x-3)=1/6(2x-7) | | sin^2x/1-cosx | | 9x^2+3x+2= | | 5=(15000/x)*1000 | | y=3x^4-11x^2+10 | | 2x-27=18-3x | | y=3x^4-11x+10 | | (3y-5)(4y-7)= | | x*7-32=115 | | X/2=3/7 | | 18=w-4w | | 0.9=22500/x | | 5=15000/x)*1000 | | 3.50=(13500/x)*1000 | | 0=-4t^2+14t+1 |